Russian University Students’ Volunteering within the Framework of Sustainable Development Goals and Values - O. V. Zinevich; E. A. Melekhina (Высшее образование в России)
The article deals with the issue of university students’ volunteering aimed at pursuing the sustainable development goals under conditions of global crisis and transformation of Russian educational policy in terms of renewal of the higher education upbringing function on the basis of traditional values of the Russian civilization. Russia’s activities on achieving sustainable development goals address carrying out infrastructure projects and Green Agenda. Although large-scale state program of volunteering support and development is being executed, volunteering for sustainable development is not given close attention. Ecological and social volunteering prioritized by governmental regulatory documents is not consistent with implementing sustainable development goals. The need to facilitate volunteering development in universities accomplishing the mission of social and economic development of society in partnership with businesses and civil society institutions is underestimated both in research and in practice. Using system and activity approaches, the authors set the goal to describe the present state of students’ ecological and social volunteering as an efficient platform for attaining sustainable development goals and necessitate its further systemic support. It is shown that the concept of sustainable development is not being an ideological orientation of volunteering practices, although students’ competences aimed at promoting common welfare could be more efficiently developed not only at theoretical level but through real volunteering for the good of future generations. In cross-sectoral partnership of universities, businesses and state, ecological and social goals are achieved by means of volunteering under the supervision of the state while Russian businesses, applying the ESG (Environmental, Social, Governance) principles, do not spare their efforts on collaborative development. As for the subjective factor impeding the development of university students’ volunteering the lack of ideological orientation towards sustainable development, which could be based on universal values specified by Russian culture codes